2018
DOI: 10.1534/genetics.118.301178
|View full text |Cite
|
Sign up to set email alerts
|

Dual Roles for Yeast Sti1/Hop in Regulating the Hsp90 Chaperone Cycle

Abstract: The Hsp90 chaperone is regulated by many cochaperones that tune its activities, but how they act to coordinate various steps in the reaction cycle is unclear. The primary role of Hsp70/Hsp90 cochaperone Sti1 (Hop in mammals) is to bridge Hsp70 and Hsp90 to facilitate client transfer. Sti1 is not essential, so Hsp90 can interact with Hsp70 without Sti1. Nevertheless, many Hsp90 mutations make Sti1 necessary. We noted that Sti1-dependent mutations cluster in regions proximal to N-terminal domains (SdN) or C-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 59 publications
(112 reference statements)
4
30
0
Order By: Relevance
“…We discovered that hHsp90α, unlike hHsp90β, was unable to complement essential yeast Hsp90 functions in our strains ( Figure 1(a) ) [ 24 ]. This inability is in contrast to previous studies from two groups that reported weak complementation by hHsp90α compared to hHsp90β [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We discovered that hHsp90α, unlike hHsp90β, was unable to complement essential yeast Hsp90 functions in our strains ( Figure 1(a) ) [ 24 ]. This inability is in contrast to previous studies from two groups that reported weak complementation by hHsp90α compared to hHsp90β [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we showed that non-lethal mutations in Hsp82 that become lethal when the co-chaperone Sti1 (Hop in humans) is absent cluster into distinct regions that define two classes of Sti1-dependent mutations [ 24 ]. One class (SdN) is at the site of Hsp70 interaction in the M domain [ 33 ], and the other (SdC) is at the junction of the M and C domains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional studies show that human mitochondrial Hsp90, TRAP1, interacts with mitochondrial Hsp70, mortalin, in BLI assays in vitro (103), consistent with the lack of a Hop homolog in mitochondria. In addition, cytoplasmic human Hsp90␤ is seen with Hsc70 in pulldown assays (104).…”
Section: Jbc Reviews: Protein Remodeling By Hsp90 and Hsp70mentioning
confidence: 99%